Pengaruh Pembelajaran Inkuiri Terhadap Keterampilan Proses Sains Siswa Kelas Vi Pada Long Term Memory - Yudistira, Yuda; Subarjah, Herman; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2019)
Science process skills are very well developed to support the daily lives of students in order to optimize the science learning that has been learned by students, but students are often difficult to remember the material that has been learned at school. This study aims to determine the effect of inquiry learning models on students' science process skills in long term memory. In this study the method that will be used is the pre-experimental method with the design chosen by one group pretest posttest. The instruments to be used are the question of science process skill and questionnaire. Pretest is done when students are in grade IV and posttest is done when students are in grade VI. The results is obtained the value of the average test different pretest and posttest in the high group using paired t-test, in the medium group using the Wilcoxon test, and in the low group using the t-test paired with p-value (Sig.)0.210 means that p-value Î± shows no change in students' science skills or still persists in long-term memory of students in the high, medium and low groups with the use of inquiry learning models. then the posttest value in all groups was calculated using the kruskal wallis test, obtained the value of Asymp. Sig 0.172 which means greater than Î±. This means that there is no difference in improvement or science process skills equally surviving in the long term memory of students in the high, medium and low groups.Â